1996
DOI: 10.4000/ries.3264
|View full text |Cite
|
Sign up to set email alerts
|

Évaluer plutôt que noter

Abstract: NOTE DE L'AUTEUR L'auteur de cet article remercie les membres du Groupe romand et tessinois d'évaluation pour leurs réflexions et leurs apports Mettre des notes, ne pas en mettre ? Telle est la question ! Mais est-ce bien là une bonne question ? Et pourquoi se poser cette question ? Noter finalement, est-ce évaluer ou seulement une façon d'exprimer les résultats de l'évaluation ? Nous montrerons que la notation chiffrée n'est pas l'évaluation, à peine l'une de ses manifestations, la plus visible peut-être, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Our present study deals with the interest of FE in the TL process at the ISPITS level in Morocco. This innovative pedagogical practice [15] needs to be introduced and situated systematically with well-established tools [16] following the example of certain countries such as Switzerland [8] and Quebec [22] which have insisted on FE in their learner training curricula. This research showed that 61.70% of teachers have a master's degree in pedagogy, which enables them to situate FE in a valid way within ISPITS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present study deals with the interest of FE in the TL process at the ISPITS level in Morocco. This innovative pedagogical practice [15] needs to be introduced and situated systematically with well-established tools [16] following the example of certain countries such as Switzerland [8] and Quebec [22] which have insisted on FE in their learner training curricula. This research showed that 61.70% of teachers have a master's degree in pedagogy, which enables them to situate FE in a valid way within ISPITS.…”
Section: Discussionmentioning
confidence: 99%
“…FE offers a new practice, where teachers can devote their energies to creating teaching tools and strategies, rather than correcting papers [15], [16]. This is true, especially among learners of HE options about sanitary engineering, like solid waste management, drinking water supply, drinking water quality control, and liquid waste management.…”
Section: Introductionmentioning
confidence: 99%
“…Notre présente étude traite l'intérêt de l'E/F dans le processus de l'E/A au niveau des ISPITS du Maroc, cette pratique pédagogique innovante [15] doit être instaurée et située d'une manière systématique avec des outils bien établis [16] à l'instar de certains pays…”
Section: Discussionunclassified
“…Bref, l'E/F propose une nouvelle pratique, où l'enseignant peut consacrer ses énergies à créer des outils et des stratégies pédagogiques, plutôt qu'à corriger des copies [15], [16] spécialement chez les apprenants de l'option S/E et ce en relation avec la génie sanitaire, en l'occurrence la gestion des déchets solides, approvisionnement en eau de boisson, Contrôle de la qualité de l'eau de boisson, Gestion des déchets liquides, Aussi pour la génie civile comme l'hygiène de l'habitat et urbanisme et autres compétences permettant la conservation et la protection de l'environnement.…”
Section: Introductionunclassified